Kondisi Sosial Ekonomi Pelaku Usaha di Objek Wisata Pantai Pasir Jambak Kelurahan Pasir Nan Tigo Kota Padang - Putri, Wulan Muhareva; Mariya, Sri (Lembaga Yasin AlSys, 2025)
The research objectives were to determine: 1) Socio-economic conditions of business actors at Pasir Jambak Beach tourist attraction; 2) The obstacles of business actors in the tourist attraction of Pasir Jambak Beach; 3) Business actors' efforts to overcome these obstacles. This research is a qualitative descriptive research. Data collection techniques are observation, interviews and documentation. The research subjects are business people who are in the tourist attraction of Pasir Jambak Beach. The data analysis technique uses the Miles and Huberman model, namely data reduction, data display and verification. The results showed: 1) Socio-economic conditions: Working as an entrepreneur by opening a business at Pasir Jambak Beach tourist attraction is the main job for business actors. The income of some business actors on weekdays ranges from Rp. 100,000- Rp. 300,000 per day depending on the number of visitors, when the holiday income has increased. The last education of business actors is high school. Based on the type of house, business actors include simple houses; 2) The obstacles of business actors are abrasion natural disasters and lack of tourist attractions; 3) Efforts to overcome them by making temporary embankments, making simple attractions, and expecting the role of the government to find solutions related to abrasion and develop tourist attractions.